Touches across time: queer as provenance - Freeman, Elliot (Archival science, 2024)
Carolyn Dinshaw describes her queer historical practice as being about looking for “an affective connection, for community, for even a touch across time” (1999, p 21). Queer engagements with records—these touches across time—are not easily or adequately accounted for in current conceptualisations of provenance. The dissonance between how we currently understand record co-creation, and the historical perspectives and recordkeeping needs of queer users, substantially and negatively impacts the visibility and accessibility of queer histories in institutional archival settings. In this paper, I articulate the proposed concept of queer as provenance. I argue that we must extend our current conceptualisation of multiple provenance beyond mere co-creatorship. With a focus on queer records and record users, I argue that we must expand our understanding to encapsulate not only the relationship between record, creator, and subject, but also the relationship between record, creator, subject, and user. Through a continuum lens, I consider how queer/ing engagements and interactions with, and responses to, queer records could and should inform our descriptive practices, and explore the potential of considering queer users as co-creators within such a dynamic. I conclude by articulating queer as provenance and consider its potential as a foundation on which transformative, reparative, and liberatory archival practices might be built.